Exploring the Science of Conducting Surveys for Studying Men’s Sexual Assault Perpetration Behaviors - Aguilar, Jemel; Mahapatra, Neely; Busch-Armendariz, Noël; Dinitto, Diana M. (Journal of Aggression, Maltreatment & Trauma, 2016)
Focus groups were used to explore the most appropriate ways to conduct survey research about men’s relationships with women and their sexual assault behaviors that result in high response rates and decrease socially desirable answers. A racially diverse group of 24 English-speaking heterosexual men, aged 18 years or older, were recruited for participation in 3 focus groups. The men were asked to review a survey instrument used in a previous study and the results from that study. Analysis of the focus group transcripts indicates that the men responded to the survey instrument from 3 distinct perspectives: (a) perpetrators, (b) victims, and (c) respondents. From these perspectives, the men also commented on participant anonymity, survey construction and delivery method, question wording, and potential pitfalls in asking men about sexual assault.
Keywords: Engaging men; dept.swk; rape or sexual assault; survey methodology

Everyone’s responsibility: Community partnerships and shared commitment for mental health promotion - Jung, Hyejin; Aguilar, Jemel P. (Social Work in Mental Health, 2016)
In this article, we use qualitative methods to understand the ways in which community involvement in a community-based mental health promotion conference encourages mental health care in an African-American community. We collected data through key informant interviews, focus groups, and participant observations at conference planning meetings and conferences, as well as archival documents related to the conference. We identify community partnerships and shared commitment as drivers of the outreach to people in the community, creators of a culturally relevant and supportive environment for mental health education, and, consequently, promoters of mental health care in the African-American community.
Keywords: African Americans; case studies; community partnerships; community-based programs; dept.swk; mental health and illness; mental health promotion

Migration and HIV among Asian Populations: Social Work interventions - Sen, S; Aguilar, Jemel (Migrant Workers: Social Identity, Occupational Challenges and Health Practices, 2016)
Worldwide labor migration has transformed and reshaped various fields of government policy and professional practices. Labor migration is associated with the non-economic social phenomena that scholars have increasingly paid attention to in both sending and receiving destinations. For practitioners in the field of education, medicine, nursing, social work, mental health, public health, and other professional practices, the human face of labor migration migrant workers and their families daily challenges often reveals the human cost of migration behind the image of economic gain and benefits. Migrant workers and their families are facing vexing challenges ranging from basic needs to psychosocial well-being, despite who they are and where they come from. Traditional ways of thinking and knowing cannot address these challenges adequately; rather, established divisions of professions, systems, disciplines, and/or areas of practice might just be the factor that constrains the ability to clearly articulate compelling problems and adds an additional layer of complexity to problem solving. This book focuses on country policies and practices, and draws on theoretical ideas that provide the intellectual basis. In addition, it offers vivid examples of how migrant workers manage to work, pursue economic security, strive and adjust in new communities, define and negotiate self and identity, and seek health and well-being. While the book illuminates shared challenges and experiences for each group of migrant workers (i.e. low-skilled workers, internal migrants and other types of migrating laborers), it also synthesises the intersectionality across all migrant workers, as they remain committed to bettering the lives of their families and communities in their origin countries as well as new host countries and communities. This volume reflects the efforts of interdisciplinary research and collaboration
Keywords: dept.swk

Is Talking About What’s Wrong Necessarily Right: A Positive Perspective on the Diagnostic Interview - O’Brien, Kyle H.; Schlechter, Alan (Journal of the American Academy of Child & Adolescent Psychiatry, 2016)
Keywords: Adolescent; Child; Child Psychiatry; Emotions; Humans; Interview, Psychological; Mental Disorders; Neurodevelopmental Disorders; dept.rec; dept.swk; peer-reviewed

A model of integrated health care in a poverty-impacted community in New York City: Importance of early detection and addressing potential barriers to intervention implementation - Acri PhD, Mary C.; Bornheimer MS, LCSW,Lindsay A.; O’Brien DHSc, MSW, MSOT, LCSW, OTR/L,Kyle; Sezer MPA, Sara; Little PsyD, LCSW-r, SAP, CCM,Virna; Cleek PhD, Andrew F.; McKay PhD, Mary M. (Social Work in Health Care, 2016)
Disruptive behavior disorders (DBDs) are chronic, impairing, and costly behavioral health conditions that are four times more prevalent among children of color living in impoverished communities as compared to the general population. This disparity is largely due to the increased exposure to stressors related to low socioeconomic status including community violence, unstable housing, under supported schools, substance abuse, and limited support systems. However, despite high rates and greater need, there is a considerably lower rate of mental health service utilization among these youth. Accordingly, the current study aims to describe a unique model of integrated health care for ethnically diverse youth living in a New York City borough. With an emphasis on addressing possible barriers to implementation, integrated models for children have the potential to prevent ongoing mental health problems through early detection and intervention.
Keywords: Child mental health; dept.rec; dept.swk; early detection and treatment; integrated care pathway; peer-reviewed

Parental Mental Health: Addressing the Unmet Needs of Caregivers for Children With Autism Spectrum Disorders - Lushin, Viktor; O’Brien, Kyle H. (Journal of the American Academy of Child & Adolescent Psychiatry, 2016)
Keywords: dept.rec; dept.swk; peer-reviewed

Evolving from an illusionary and self destructive quest for power to a state of empowerment: The curative potential yoga may hold as a vehicle to reclaiming bodily empowerment for women with anorexia - Pizzanello, H.C. (Journal of Sociology and Social Welfare, 2016)
Eating disorders disproportionately afflict women and they are one of the most lethal mental health conditions that practitioners in the field of social work and related mental health fields encounter. Equally alarming is the fact that Anorexia Nervosa is the deadliest of all eating disorders, yet, we are struggling to find an efficacious means of successfully intervening in the treatment and recovery maintenance of anorexia. Drawing from past empirical and theoretical literature, this study explored the potential that the mind body practice of yoga might hold as a complementary therapeutic tool for women struggling to recover from anorexia. The findings that emerged from the analysis of this study’s data indicate that yoga can play a curative role with this population. The findings also revealed that yoga’s primary efficacy resides in its potential to facilitate an experience of connected acceptance and feelings of empowerment in this population of women. © 2016, Western Michigan University. All rights reserved.
Keywords: Anorexia; Feminism; Therapeutic intervention; Yoga; dept.swk; ⛔ No DOI found

Being on the mat: a process evaluation of trauma-informed yoga for women with substance use disorders - Smoyer, Amy (The Journal of Sociology & Social Welfare, 2016)
Yoga practice is associated with positive health outcomes, including benefits related to managing substance use disorders and trauma symptomology. However, low-income vulnerable communities have limited access to yoga. This process evaluation of a trauma-informed yoga program for women with substance use disorders demonstrates the feasibility and utility of using noncertified yoga instructors to offer a basic yoga in community-based agencies. Participants describe outcomes related to relaxation, mindfulness, and movement that are well-aligned with their recovery needs. Study findings suggest the utilization of instructors with minimal training has the potential to expand research about and access to yoga among marginalized communities. © 2016, Western Michigan University. All rights reserved.
Keywords: Evaluation; Qualitative; Substance use; Women; Yoga; dept.swk; ⛔ No DOI found

Mapping prison foodways - Smoyer, A.B. (Experiencing imprisonment: research on the experience of living and working in carceral institutions, 2016)
Keywords: dept.swk

Making fatty girl cakes: food and resistance in a women's prison - Smoyer, Amy B. (The Prison Journal, 2016)
This article builds on existing knowledge of inmate resistance by analyzing formerly incarcerated women's narratives about prison food. Participants described trying to secure extra cafeteria portions, hoarding food, smuggling and stealing food, and cooking and eating in the cellsall to resist prison power and gain some control over their lives by managing what, how, when, and with whom they ate. These data shed light on prison life and suggest changes to food policy to curb inmate resistance and bolster the rehabilitative potential of correctional facilities.
Keywords: dept.swk; food; prisoners; resistance; women

Applying research to enhance capacity: A unifying purpose for an integrated profession - Keenan, Elizabeth King (Journal of Social Work Education, 2016)
For more than a century the social work profession has had a dual purpose: to promote individual well-being and social justice, but the micro-macro divide is fragmenting the profession. This article suggests that the profession's aim might best be realized by adopting a unifying purpose, a just sense of well-being. Research on complex adaptive systems conceptualizes a unifying purpose as vertical integration carried out in differentiated ways in discrete moments of practice in various settings. Interpersonal neurobiology and Aristotle's interdependence of character virtues and practical judgment inform a corresponding shift from the dualities of personal and professional to the social worker as a person with differentiated professional capacities and activities. Integration with differentiation enhances capacity to promote the profession's purpose.
Keywords: dept.swk; differentiation; human; human experiment; morality; neurobiology; occupation; peer-reviewed; social justice; social work; wellbeing

Meeting at the thin places: synchronicities in clinical practice - Schneider, Dana A. (Smith College Studies in Social Work, 2016)
Unusual events, beyond mere coincidences, may occur during the course of psychotherapy. Yet, clinical training often does not prepare therapists how to understand and potentially engage with these encounters. The aim of this report is to explore the emergence of synchronistic events in therapy, while providing two clinical case composites to illustrate the author's central points. Drawing on the Celtic concept of thin places, a new understanding of synchronicities and the therapeutic relationship is offered.
Keywords: Internal structure; dept.swk; synchronicity; therapeutic relationship; thin places; unconscious communication; unknown